EUS-Guided Choledochoduodenostomy for Biliary Drainage in Unresectable Pancreatic Cancer: A Case Series - Artifon, Everson L A; Takada, Jonas; Okawa, Luciano; Moura, Eduardo G H; Sakai, Paulo (JOP. Journal of the Pancreas, 2010)
Context Endoscopic retrograde cholangiopancreatography (ERCP) is the procedure of choice for biliary decompression in patients with unresectable pancreatic cancer. However, it may be unsuccessful in 3 to 10% of cases. When ERCP is unsuccessful, the usual alternatives are percutaneous transhepatic biliary drainage or surgery. Recently, several authors have reported the use of EUS-guided biliary drainage in patients with malignant biliary obstructions, with acceptable success and complication rates. We describe three cases of unresectable pancreatic cancer associated with obstructive jaundice, treated by EUS-guided biliary drainage. Case report Three patients with unresectable pancreatic cancer, associated with obstructive jaundice, were included. ERCP was unsuccessful because of complete tumor obstruction of the distal common bile duct and papilla invasion. An EUS-guided rendezvous maneuver was attempted, without success. Then, EUS-guided choledochoduodenostomy, with a partially covered self-expanding metal stent, was performed in the same procedure. There were no early complications and the procedure was also clinically effective in relieving jaundice in all cases. Conclusions EUS-guided biliary drainage is a feasible alternative to percutaneous transhepatic biliary drainage or surgery in unresectable pancreatic cancer with obstructive jaundice when ERCP fails. However, the development of new specific instruments and studies comparing this procedure with percutaneous transhepatic biliary drainage and surgery are needed. Image: Endoscopic view of transduodenal self-expandable metallic stent.